If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 4 = 3 * 4 Reorder the terms: 4 + 3x = 3 * 4 Multiply 3 * 4 4 + 3x = 12 Solving 4 + 3x = 12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 3x = 12 + -4 Combine like terms: 4 + -4 = 0 0 + 3x = 12 + -4 3x = 12 + -4 Combine like terms: 12 + -4 = 8 3x = 8 Divide each side by '3'. x = 2.666666667 Simplifying x = 2.666666667
| -7w^4(2w^4-5)= | | -21=-5x+6x-1 | | 10x+7=2x-5 | | 9y=x+4 | | -10m+3=13-2m-6m | | 3(6y-6)-(2y-7)= | | 3x=54-3y | | (x+2)(y^2+2y-12)= | | 3(a-5)=27 | | 5+n=23 | | (x+2)(y^2+2y-12)=equation | | 8.6=9.8-0.3x | | x^3+0.5x^2-2x+6=0 | | 17=3(g+3) | | 7x^2+5x+16=0 | | -x^3+7x^2-8x+12=0 | | m+30.3=40.8 | | 30.3+m=40.8 | | f(x)=x^4-2x^3-8x^2 | | 3(5c-6)=36 | | 15y=75 | | 2p-5=6+4p | | -10-6(-30)= | | (n+6)(n+3)=0 | | 2y=8x-10 | | A^2b^2-100=0 | | 4.8n+5.2n=7 | | 2x+3=3x+18 | | f(x)=16x+12 | | 4n+5.8=3 | | 2x+5=2(2x+5) | | -48+x+6x=92 |